Esophageal atresia: metaplasia, Barrett. Issue 4 (16th May 2013) - Schneider, A.; Michaud, L.; Gottrand, F.
Summary Barrett's esophagus is characterized by the replacement of squamous epithelium by columnar epithelium that is intestinal metaplasia‐positive or ‐negative in the distal esophagus. Gastroesophageal reflux disease, which is frequent and prolonged in esophageal atresia, probably plays a major role in the development of Barrett's esophagus through repeated mucosal damage. Long‐term acid exposure contributes to carcinogenesis in Barrett's esophagus of intestinal type, but its effect on gastric metaplasia is less well defined. Recent studies have suggest that metaplasia arises in about 15% of patients with esophageal atresia, with a lag time to developing metaplasia from initial surgical correction of about 10 years. Preliminary data from an ongoing multicenter study including 88 patients with esophageal atresia aged 15–19 years showed gastric metaplasia in 42% of patients (29 fundic and 7 cardial metaplasia), while one patient presented intestinal metaplasia. Esophageal mucosal abnormalities can be observed in esophageal atresia patients at endoscopy despite the absence of symptoms. Whether prolonged, aggressive, acid suppression is beneficial in these situations remains to be determined. Barrett's metaplasia can be removed by endoscopic mucosal resection or destroyed with endoscopic ablative techniques, such as photodynamic therapy, radiofrequency ablation, and cryotherapy. The risk of developing esophageal carcinoma is still a controversial issue as only a few clinical cases have been reported in young adults with esophageal atresia. As late complications of esophageal atresia, particularly esophagitis and Barrett's esophagus, are increasingly being recognized, long‐time systematic follow up of the esophageal mucosa including multistage biopsies is therefore required even in asymptomatic patients.